Anti-fibrotic effect of black tea (Camellia sinensis) extract in experimental pulmonary fibrosis. (February 2019) - Chakraborty, Kaustav; Dey, Avijit; Bhattacharyya, Arindam; Dasgupta, Subir Chandra
Graphical abstract: Highlights: Black Tea Extract (BTE) reduces collagen deposition in pulmonary fibrosis. BTE downregulates TGF-β expression in bleomycin-induced pulmonary fibrosis. BTE inhibits the fibroblast to myofibroblast transformation in BIPF. BTE upregulates IFN-γ expression in bleomycin-induced pulmonary fibrosis. BTE affects on apoptotic markers in experimental pulmonary fibrosis. Abstract: There is no effective therapy exists for Idiopathic pulmonary fibrosis (IPF) till now. Few studies have been done on protective effects of green tea in pulmonary fibrosis but there is no single report on black tea extract (BTE) in pulmonary fibrosis so far. This study aims to investigate the anti-fibrotic effect of BTE against experimental pulmonary fibrosis. Four groups of animals were selected for this study. Group 1: control group mice. Group 2: mice exposed to bleomycin for 21 days, Group 3 and Group 4: bleomycin exposed mice treated with 25 mg BTE/kg b.w./day, p.o and 50 mg BTE/kg b.w./day, p.o. respectively for 21 days. Bleomycin exposed mice showed increased collagen deposition and wet/dry weight ratio, which were attenuated upon 50 mg BTE/kg b.w. treatment. The increased level of histopathological parameters in bleomycin-induced mice was significantly decreased after 50 mg BTE/kg b.w. treatment. Furthermore, 50 mg BTE/kg b.w. administration also decreased the expression of α-SMA in bleomycin-induced mice. This treatment with 50 mg BTE/kg b.w. also down regulated the expression of TGF-β and up regulated IFN-γ expression in experimental pulmonary fibrosis. The results of the present study put-forward BTE as a potential anti-fibrotic agent due to its attenuating effect on potential fibrotic markers.